2004
DOI: 10.1007/s11936-004-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of fetal tachyarrhythmias

Abstract: Fetal tachyarrhythmias are an important cause of fetal morbidity and mortality. The majority of fetal tachyarrhythmias are due to atrioventricular reentrant type of supraventricular tachycardia and atrial flutter. Fetal echocardiography remains the main tool of diagnosing and discerning the mechanism of tachyarrhythmia. The goals of therapy for fetal arrhythmias are to restore sinus rhythm, resolve heart failure, and postpone delivery before term. Although there is no anonymity in the approach to the drug trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…While fetal arrhythmias are typically isolated findings, around 5% of cases may also involve congenital heart diseases. 26,27 In our study, all identified tachyarrhythmias were isolated without associated SHD or tumors.…”
Section: Tachyarrhythmiasmentioning
confidence: 56%
“…While fetal arrhythmias are typically isolated findings, around 5% of cases may also involve congenital heart diseases. 26,27 In our study, all identified tachyarrhythmias were isolated without associated SHD or tumors.…”
Section: Tachyarrhythmiasmentioning
confidence: 56%
“…Nevertheless, it is still important to be aware of tachycardia. Tachyarrhythmias, including tachycardia, are mainly caused by maternal infection or fetal hypoxia and can be lethal despite specific treatments [16, 17]; sustained fetal tachycardia might lead to fetal heart failure, hydrops, and polyhydramnios [11].…”
Section: Discussionmentioning
confidence: 99%
“…3 If undiagnosed and untreated, foetal tachycardia may lead to low-output cardiac failure and hydrops, thereby increasing foetal morbidity and mortality. [4][5][6] Ultrasonography can diagnose both, the abnormal foetal heart rate as well as the hydrops. 5,6 However, since foetal tachyarrhythmias are amenable to transplacental as well as direct foetal pharmacologic therapy, it is essential that the pregnant woman be transferred to a tertiary care centre with facilities for foetal echocardiography and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Digoxin is the usual first-line drug while sotalol, flecainide and amiodarone have been used as second-line drugs. 3,4,9 In a review of published studies, out of 314 cases of foetal SVT, Krapp and colleagues reported digoxin to be significantly less effective in the treatment of SVT in foetuses with hydrops (24.6% success) as compared to foetuses without hydrops (65.4% success). 9 Another study on refractory cases of foetal tachycardia reported a success rate of 93% in the treatment of foetal SVT in hydropic foetuses using amiodarone.…”
Section: Discussionmentioning
confidence: 99%